Coaching Experts: Applications to Surgeons and Continuing Professional Development. (February 2018) - Zahid, Assad; Hong, Jonathan; Young, Christopher J.
Surgery is a science and an art, which is mastered through years of training and refined by the accumulation of individual experience and preference. Continuing professional development (CPD) is a concept that emphasizes a self-directed approach to education. Coaching is a process that leads to increased utilization of a person's current skills and resources without counselling or advising. Coaching in surgery could be used to facilitate and optimize feedback and reflection, thus enhancing performance and outcomes through elite performance of an operative procedure. Therefore, it can be applied under the umbrella of CPD. Ultimately also emphasizing that better quality surgery is not necessarily purely based on technical outcomes, it is a combination of both technical and nontechnical practice. Coaching of surgeons is a conceptually formidable tool in the successful implementation of effective CPD programs. CPD currently provides an opportunity for surgeons to gain access to constantly evolving medical knowledge and technique; however, there is no accountability to its understanding or implementation. Coaches have the potential to provide confidential appraisal and feedback in a constructive approach with the aim to eliminate any barriers to the transfer of technique and knowledge.